Biorefinery for tuna head wastes: Production of protein hydrolysates, high-quality oils, minerals and bacterial peptones. (10th July 2022) - Vázquez, José Antonio; Pedreira, Adrián; Durán, Salvador; Cabanelas, David; Souto-Montero, Paula; Martínez, Paula; Mulet, Mercedes; Pérez-Martín, Ricardo I.; Valcarcel, Jesus
Abstract: The canning industry plays a crucial role in the sector of marine foods, but produces several organic wastes and effluents with reduced economic value that must be upgraded to comply with the circular bioeconomy principles. Initially, we have searched the best experimental conditions for the hydrolysis of upper and lower halves from yellowfin tuna ( Thunnus albacares ) heads by four commercial proteases (alcalase, papain, protamex and esperase). Then, optimal conditions were corroborated at 5 L pH-Stat reactor producing fish oil, bones and fish protein hydrolysates (FPH). Alcalase and esperase applied on upper head were the options that led to the largest volumes of oils recovered, and the highest degrees of hydrolysis, digestion yields and concentrations of protein in FPH. Fish oils showed an excellent content in omega-3 fatty acids, mainly the highly valued docosahexaenoic acid (DHA). In the case of FPH, the proportion of human essential amino acids was higher than 40% and the average protein size in the interval 1400–1800 Da. Finally, these hydrolysates were incorporated, as source of protein material in substitution of commercial peptones, in two types of bacterial culture media (marine and Man-Rogosa-Sharpe, MRS). The bioproductions of the four bacteria assayed (two lactic acid bacteria and two marine probiotic bacteria) in the low-cost media formulated with tuna hydrolysates were generally similar or even higher than found in commercial broths. The whole of these results evidenced the validity of the present proposal, aimed to the integral production of valuable biocompounds, in order to contribute to a more sustainable tuna canning industry. Graphical abstract: Image 1 Highlights: Valorization of tuna head by-products yields protein hydrolysates, oil, and minerals. Optimization of proteolysis allows the establishment of the best reaction conditions. Oils and protein hydrolysates are rich in ω-3 and essential amino acids respectively. Low cost protein hydrolysates appear suitable as substitutes of commercial peptones. These biocompounds may contribute to the sustainability of the canning industry.